Prevalence and Nature of Trauma and Injuries in Karachi National Trauma Registry of Pakistan â€œThe Need of the Hourâ€ (Journal of Pakistan Orthopaedic Association, 2017)
ABSTRACTObjective: To assess the prevalence, nature of trauma, reason(s) behind these trauma and first-aid care provided during transportation to hospital in Karachi Pakistan. Study also presents the framework of a national trauma registry and comparatively analyzes data between other registries.Method: This cross sectional observational / descriptive study was conducted from July 2015 to Dec 2015. An informed verbal consent was taken and preformed questionnaire was filled. Patient brought dead and who did not give consent were excluded. Data was analyzed using SPSS 21 for statistical significance.Results:  The study conducted on 1500 patients includes 1030 males (68.7%) and 470 females (31.3%). Mean age was 45 SD 28.69Maximum injuries occurred in age group of 11-20 year. By occupation most were found to be students & children 350(23.3%). Most traumas occurred on road 919(61.3%) and other occurred in home 349(22.7%). Road traffic accidents are found to be major cause of injuries 730(48.7%) and rest was due to other causes 630(42.0%).The vehicle involved in majority of cases was motorcycle 340(22.7%). In most of the cases emergency medical service 72148.0% was used for the transportation of the patients. During transportation (100%) of victims were not provided with first aid, breathing care/ bleeding care/iv fluids and splints/slabs. Severity at emergency room of patients was mainly moderate (52.7%) while severe condition was suffered by (32.0%) of patients and mild (14.7%).Conclusion: This study concluded that the transport accidents are the major health problems especially in young population in Karachi. For better transportation of patients it is needed to upgrade facilities of ambulances and other emergency medical services. Emergency medical care facilities (including emergency trauma centers) establishment at district level, sub-divisional level are needed to provide good and quality care to trauma patients. Improvement in trauma care depends on the establishment of functioning trauma care systems, of which a trauma registry is a crucial component